Growth patterns and clinical outcomes in association with breastfeeding duration in HIV exposed and unexposed infants: a cohort study in KwaZulu Natal, South Africa - Larisha Pillay; Dhayendre Moodley; Lynda Marie Emel; Ntombifikile Maureen Nkwanyana; Kimesh Naidoo (BMC, 2021)
Abstract Background Exclusive breastfeeding for 6 months and breastfeeding with complementary feeds until 12 months for HIV exposed and uninfected (HEU) infants or 24 months for HIV unexposed (HU) infants is the current World Health Organisation (WHO) recommendation for low and middle income countries (LMICs) to improve clinical outcomes and growth trajectories in infants. In a post-hoc evaluation of HEU and HU cohorts, we examine growth patterns and clinical outcomes in the first 9 months of infancy in association with breastfeeding duration. Methods Two cohorts of infants, HEU and HU from a low-socioeconomic township in South Africa, were evaluated from birth until 9 months of age. Clinical, anthropometric and infant feeding data were analysed. Standard descriptive statistics and regression analysis were performed to determine the effect of HIV exposure and breastfeeding duration on growth and clinical outcomes. Results Included in this secondary analysis were 123 HEU and 157 HU infants breastfed for a median of 26 and 14 weeks respectively. Median WLZ score was significantly (p < 0.001) lower in HEU than HU infants at 3, 6 and 9 months (− 0.19 vs 2.09; − 0.81 vs 0.28; 0.05 vs 0.97 respectively). The median LAZ score was significantly lower among HU infants at 3 and 6 months (− 1.63 vs 0.91, p < 0.001; − 0.37 vs 0.51, p < 0.01) and a significantly higher proportion of HU was classified as stunted (LAZ < -2SD) at 3 and 6 months (3.9% vs 44.9%, p < 0.001; 4.8% vs 20.9%, p < 0.001 respectively) independent of breastfeeding duration. A higher proportion of HEU infants experienced one or more episodes of skin rash (44.5% vs 12.8%) and upper respiratory tract infection (URTI) (30.1% vs 10.9%) (p < 0.0001). In a multivariable analysis, the odds of occurrence of wasting, skin rash, URTI or any clinical adverse event in HEU infants were 2.86, 7.06, 3.01 and 8.89 times higher than HU infants after adjusting for breastfeeding duration. Conclusion Our study has generated additional evidence that HEU infants are at substantial risk of infectious morbidity and decreased growth trajectories however we have further demonstrated that these adverse outcomes were independent of breastfeeding duration.